Особенности взаимоотношений видов кормовых растений в двухкомпонентных сеяных сообществах - Глухов, А.З.; Юрченко, И.Т.; Кохан, Т.П. (Промышленная ботаника, 2002)
The competitive capacity of 7 perennial fodder plant species has been revealed. The species are arranged into the row of increasing competitive capacity: Trifolium pratense L. ‘Skif 1’, Medicago sativa L. ‘Veselopodolyanskqja 11’, Agropyron pectinatum (Bieb.) Beauv., Phleum phleoides (L.) Karst., Dactylis glomerata L., Arrhenatherum elatius (L.) J. et C. Presl, Festuca regeliana Pavl. The index of the degree of overlapping the ecological niches is determined for the species investigated, that enables to ascertain the expediency of the species employing for the fodder agrophytocenoses.